Predictors of metabolic syndrome among polycystic ovary syndrome sisters - Bindu Kulshreshtha; Neera Sharma; Shubhi Pant; Akhila Prasad; Anubhuti Chitkara; Bhawna Pahuja; Isha Pahuja (Wolters Kluwer Medknow Publications, 2019)
Aims: Metabolic syndrome among PCOS sisters may vary depending on the phenotype. The aim of the present study was to analyze the prevalence of metabolic syndrome among different phenotypes of PCOS sisters. Design: Case control study. Materials and Methods: Two hundred sisters of PCOS patients and 99 age matched healthy controls underwent history, clinical examination, biochemical parameters for metabolic syndrome and hormonal assessment. Results: Of 200 sisters, 85 were unaffected (UA group), 21 sisters had hyperandrogenemia (HA group), and 94 sisters had irregular periods or hyperandrogenemia. We observed that the frequency of metabolic syndrome among PCOS sisters was comparable to age and weight matched controls (30% vs 27%). The prevalence of metabolic syndrome was higher in HA and AFFECTED sisters (around 30% in both) compared to UA sisters (20%). The presence of metabolic syndrome was significantly associated with age, BMI, HOMA-IR and free testosterone. After correction for age and BMI, metabolic syndrome was significantly associated with HOMA-IR (P - 0.05) and free testosterone (P - 0.03). Conclusion: Based on above findings, we conclude that affected sisters and those with higher age, BMI and hyperandrogenemia have a high risk of metabolic syndrome compared to unaffected sisters.